Peningkatan Mutu Keselamatan Pasien Melalui Digitalisasi Pelaporan Insiden Keselamatan Pasien - Saefulmilah, Henik; Marlina, Eli; Sundari, Pini; Nopianna, Inna (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to build and strengthen the IKP reporting system, improve the culture of reporting in the event of a patient safety incident, and learn from the incidents that occur. The method used is through the Plan-Do-Check-Action (PDCA) cycle approach. The study's results showed the perception that officers did not report IKP because of fear of disciplinary action, the absence of reporter anonymity, and confidentiality was not maintained. Based on the identification results, an intervention plan was prepared to develop IKP reporting through digital media. The intervention results showed an increase in IKP reporting to 34 reports in one month of the IKP reporting digitalization trial period. In conclusion, the intervention proved successful in one PDCA cycle. There needs to be socialization, monitoring, and evaluation of the implementation of the IKP reporting flow SOP periodically to improve the reporting culture and the quality of service that prioritizes patient safety. Keywords: Patient Safety Incident, Reporting